„Tag ěto viřísení”. On Forms and Functions of Graphic Language Devices - Mareš, Petr (Poznańskie Studia Slawistyczne, 2017)
Normally, the sequences of graphic language devices function as “building material” for morphemes and words. Nevertheless, these sequences sometimes (especially in literary texts) occur in defamiliarized forms. The paper describes how the defamiliarized sequences of graphic devices are used in several texts written by Czech authors and how they can be interpreted by recipients. A specific way of use of graphic devices can represent the intellectual level of a character, evocate the course of spoken utterances, reveal the conventionality of orthographic rules, etc.